Body Perceptions of Female Athletes Aged Between 11 and 14 - Şakar, Murat; Bayındır, Melek; Kılıç, Tahir (Progress in Nutrition, 2021)
Study Objectives: This study aimed to examine the body perception levels of women aged between 11 and 14, including those not playing sports and playing sports according to their sports branches. Method:  the study was carried out with 140 female participants between ages 11 and 14. The study group consists of 80 licensed women athletes playing volleyball (n:28), basketball (n:25), badminton (n:9), and swimming (n:18) and also 60 women who are educated in the same school but do not actively play sports. Participants were included in the study voluntarily. The data were measured for the 2017-2018 academic calendar by using the "The Multidimensional Body-Self Relations Questionnaire (MBSRQ)". The Turkish validity and reliability of this scale were performed. Results: The appearance orientation scores of individuals who play individual and team sports were found to be significantly lower than those who do not. It was observed that there was a significant difference in the body perception levels of women playing and not playing sports. Moreover, there was a significant difference between the fitness evaluation, fitness orientation, and overall scale scores according to age, branch, and sports status. On the other hand, there was no significant difference between the scores of appearance evaluation, health orientation, body areas satisfaction, appearance orientation, and health evaluation. Conclusion: The formation of a positive body image can be achieved by actively participating in sports and physical activities in adolescence. It should be encouraged as a state policy that adolescents participate in social sportive communities where they can establish healthy relationships. To have adult behaviors and to struggle with life, for individuals with reduced anxiety levels, high self-esteem and self-confidence, and satisfaction with their body image, organized planning and precautions should be performed to adapt them to life.